Case management intervention with violent offenders : an action research approach to the development of a practice model : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University - Dale, Michael Philip (Massey University, 1997)
This research is concerned with the relationship between social work theory and social work practice. The practice context for the discussion is intervention with men who have been convicted of violence towards their respective female partner. The agency context is the Community Corrections Service in New Zealand. The central argument surrounds the development of an integrated model of practice, one which combines a valid theoretical base with appropriate practice skills to ensure that service delivery can meet the identified needs of the relevant stakeholders (in this case the agency, practitioners, clients and victims). The introduction frames the issue of domestic violence as a key practice area and identifies concerns regarding current practice in the Community Corrections Service. The importance of using theory based intervention models is noted and the research process is outlined. In Chapter Two the broad Community Correction Practice context is reviewed. The influence of changes in four key areas are considered: Central Government Management; legislation; organisational structure, and Community Corrections Service policies. Discussion also focuses upon the challenge which the changes present to the implementation of a practice model derived from an integrated position. The Integrated Domestic Violence Practice Model (IDVPM) developed as part of this investigation forms the subject of the third chapter, which is presented in three interrelated sections. In the first section the relationship between social work theory and practice is explored and five key debates are considered (the influence of the scientific model, the influence of values, the integration of theory and practice, the utility of eclecticism and the notion of empowerment). A framework for integrated practice is then presented which seeks to define how the substantive issues surrounding the relationship between social work theory and practice can be incorporated into the day to day actions of practitioners in the field. In the final section the IDVPM is presented. This section includes consideration of the three distinct areas of knowledge from which the model has been developed: domestic violence practice theory; a case management perspective; and issues surrounding the assessment of effectiveness. Each stage of the model is outlined and linkages back to the underlying theoretical premises are indicated. Chapter Four contains the research design. First, the theoretical perspective which informs the research methodology is presented. This discussion traverses the positivist and interpretivist research traditions and grounded theory. Second, the field of action research methodology is outlined, including the rationale for the methodology, and issues surrounding its validity are addressed. Finally, the structure of the research process is presented and ethical issues involved in the research are considered. In Chapter Five the data generated through the research are presented and analysed. There follows in Chapter Six a review of the substantive themes which have emerged from the research data. This discussion is presented in three parts. The structure of the IDVPM is considered first, and recommendations for change are made. Next the influence of values upon practice and the concept of empowerment are reflected upon in relation to the research findings. Finally issues surrounding the assessment of effectiveness are re-visited. A concluding comment positions the IDVPM in relation to initial assumptions regarding the nature of case management. The final chapter provides some concluding observations regarding the research process and offers suggestions for future research. The distinctive features and implications of the Probation Officer, client and victim perspectives are also reviewed. Finally comment is made regarding what has been learnt regarding the relationship between theory and practice and the concept of integrated practice.
Keywords: Social case work; Family violence; Victims; Prevention; New Zealand